ANALISIS RASIO KEUANGAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH (APBD) KOTA MANADO UNTUK MENILAI KINERJA KEUANGAN PEMERINTAH KOTA MANADO TAHUN ANGGARAN 2011 - 2015 - Pilat, Juddy Julian; Morasa, Jenny (Universitas Sam Ratulangi, 2017)
This study aims to assess the financial performance of Manado City Government using Financial Ratio Analysis of Regional Budget for Fiscal Year 2011-2015. Type of research is the descriptif qualitative with case study approach. The processed data is the Budget Realization Report of Manado City Government for Fiscal Year 2011-2015 were obtained from the internet publication on the official website of Financial Management Board and Regional Property of Manado City. The analysis used to analyze the Regional Financial Performance is Financial Ratio Analysis by calculate the Ratio of Independence, Degree of Fiscal Decentralization, Ratio of Effectiveness, Ratio of Efficiency and Ratio of Expenditure Congruence. While the analysis used to analyze the Ability of Regional Finance is to calculate the Share and Growth, Map of Regional Finance Capability and Financial Capability Index. Based on the calculation and analysis of the Regional Financial Performance can be concluded that the pattern of the region's autonomy level relationships in Manado City is instructive criteria. Degree of Fiscal Decentralization is still lacking, but the Ratio of Effectiveness is very effective and the Ratio of Efficiency is also very efficient. Ratio of Expenditure Congruence shows the balance between expenditures are not balanced. Based on the calculation and analysis of the Regional Financial Capability can be concluded, that the condition of financial ability of Manado City is still not ideal. Share and Growth calculation results, the position of Manado City is in quadrant II and Financial Capability Index of Manado City is high. Keywords: Financial Ratio Analysis of Regional Budget, Financial Performance of Local Government.